Globalization and Economic Diversification Policy Challenges for Economies in Transition - Vos, Rob; Koparanova, Malinka (The United Nations Series on Development, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. This volume brings together new contributions from renowned academic scholars, from experts on economies in transition and from the United Nations, the European Union, the European Bank for Reconstruction and Development as well as other international agencies. It aims to answer fundamental questions and spell out policy options to address the challenges for economies in transition. The volume includes comparative studies focusing on all transition economies, including Central and Eastern Europe, as well as regions such as Western Balkans and the Commonwealth of Independent States.